2004
DOI: 10.1211/0022357023493
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the synaptosomal uptake inhibition of serotonin by St John's wort products

Abstract: Although the number of prescriptions for psychotropic drugs has decreased in recent years, prescriptions for antidepressants are still increasing (Fritze 2002). Hypericum perforatum (St John's wort) is the main psychotherapeutic herbal medicinal product used for treatment of mild-to-moderate depression. The lipophilic constituent hyperforin (2-5% of the extract) demonstrated, similarly to chemical antidepressants, a significant effect on the synaptosomal uptake inhibition of several neurotransmitters in in-vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 23 publications
(26 reference statements)
0
8
0
Order By: Relevance
“…16 HF is the main component responsible for the antidepressant effects, yet other constituents may be involved. 3,17 Hypericin and pseudohypericin as well as several flavonoids interact in vitro with various amine receptors and transporters, showing that several substances in SJW are potential central nervous system psychoactive agents and may contribute to the antidepressant efficacy of the plant. 18 However, HF is the main reuptake inhibitor, with half-maximal inhibitory concentrations for the synaptosomal uptakes of serotonin, norepinephrine and dopamine between 80 and 200 nmol/l.…”
Section: Antidepressant Effectmentioning
confidence: 99%
“…16 HF is the main component responsible for the antidepressant effects, yet other constituents may be involved. 3,17 Hypericin and pseudohypericin as well as several flavonoids interact in vitro with various amine receptors and transporters, showing that several substances in SJW are potential central nervous system psychoactive agents and may contribute to the antidepressant efficacy of the plant. 18 However, HF is the main reuptake inhibitor, with half-maximal inhibitory concentrations for the synaptosomal uptakes of serotonin, norepinephrine and dopamine between 80 and 200 nmol/l.…”
Section: Antidepressant Effectmentioning
confidence: 99%
“…The pharmacologically active ingredients of SJW are the phloroglucinol derivatives hyperforin and adhyperforin, the naphthodianthrones hypericin and pseudohypericin, the flavonoids hyperoside, rutin, quercitrin, isoquercitrin and biapigenin and the tanning agent procyanidin. Published data strongly indicate that, beside hyperforin, hypericins and some flavonoids contribute to the antidepressant effect of the extract [1,[6][7][8][9][10][11][12][13]. Flavonol glycosides (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Products containing the same botanical species [e.g., Hypericum perforatum (St. John's wort)] often contain varying amounts of the plant's marker/active 6 constituents. For example, research has shown that commercial products of the following botanical species contain varying levels of their respective constituents: Hypericum perforatum (St. John's wort) [42,43], Camellia sinensis (Green tea) [41], Tanacetum parthenium (Feverfew) [37e39], Eleutherococcus senticosis (Siberian ginseng), Panax quinquefolius (American/Canadian ginseng) [34], Hydrastis canadensis (Goldenseal) [44], and Paullinia cupana (Guarana) [45]. As a result, the pharmacological properties and in vitro activities may vary between different products (e.g., Refs.…”
Section: F Practitionermentioning
confidence: 99%